Value addition, nutritional status and shelf-life of cocoa, cardamom and sugar free dietary fiber supplement - TRILOKIA, MEENAKSHI; GANDHOTRA, ANURADHA; KUMAR, RAKESH; BAKSHI, PARSHANT (The Indian Journal of Agricultural Sciences, 2016)
At present, supplementation of food is of great interest because of increasing nutritional awareness among the consumers. Supplementation with bengal gram is one way to meet the needs of dietary fiber particularly in convenient foods. Hence, an attempt has been made to develop value added dietary fiber supplement with acceptable sensory attributes. Three types of dietary fiber supplements, viz. cardamom flavor, cocoa flavor and sugar free flavor were developed. Cardamom flavor dietary fiber supplement was developed by the addition of bengal gram, fox nut, almonds, powdered sugar and cardamom powder at different levels. Cocoa flavor dietary fiber supplement was developed by the addition of cocoa powder with same ingredients whereas, the sugar free dietary fiber supplement was prepared without the addition of sugar with same ingredients. The nutritional and storage quality evaluation of the best accepted dietary fiber supplement were estimated. The findings indicated that cocoa flavor dietary fiber supplement prepared with bengal gram (25.6 g), fox nut (25.6 g), almonds (12 g) powdered sugar (28 g) and cocoa powder (8.8 g), cardamom flavor dietary fiber supplement with same ingredients at same ratio was best accepted, as compared to the sugar free dietary fiber supplement. Among the various types of dietary fiber supplements, cocoa flavor dietary fiber supplement was most accepted. There were significant increases in appearance, flavor, taste, over all acceptability and moisture; whereas, fat, total ash, crude fiber found to be constant. The developed dietary fiber supplement has a shelf-life of two and half months.